A Wavelet Approach For Analysing The Relationship Between Exchange Rate And Interest Rate Differential - DHAMOTHARAN, LALITHA (2017)
The relationship between exchange rate and interest rate differential remains one of the most debated areas in macroeconomics. The relationship is often derived from the purchasing price parity and uncovered interest rate parity theories. An evaluation of the empirical research reveals contradictory findings with inconclusive results. First, most of the empirical studies posit a linear relationship between the variables. However, nonlinearities may exist due to market frictions. Second, most of such studies utilise the conventional econometric approach that is limited by its one-dimensional analysis.